The influence of inspiratory effort and emphysema on pulmonary nodule volumetry reproducibility. Issue 11 (November 2017) - Moser, J.B.; Mak, S.M.; McNulty, W.H.; Padley, S.; Nair, A.; Shah, P.L.; Devaraj, A.
Abstract : Aim: To evaluate the impact of inspiratory effort and emphysema on reproducibility of pulmonary nodule volumetry. Materials and methods: Eighty-eight nodules in 24 patients with emphysema were studied retrospectively. All patients had undergone volumetric inspiratory and end-expiratory thoracic computed tomography (CT) for consideration of bronchoscopic lung volume reduction. Inspiratory and expiratory nodule volumes were measured using commercially available software. Local emphysema extent was established by analysing a segmentation area extended circumferentially around each nodule (quantified as percent of lung with density of –950 HU or less). Lung volumes were established using the same software. Differences in inspiratory and expiratory nodule volumes were illustrated using the Bland–Altman test. The influences of percentage reduction in lung volume at expiration, local emphysema extent, and nodule size on nodule volume variability were tested with multiple linear regression. Results: The majority of nodules (59/88 [67%]) showed an increased volume at expiration. Mean difference in nodule volume between expiration and inspiration was +7.5% (95% confidence interval: –24.1, 39.1%). No relationships were demonstrated between nodule volume variability and emphysema extent, degree of expiration, or nodule size. Conclusion: Expiration causes a modest increase in volumetry-derived nodule volumes; however, the effect is unpredictable. Local emphysema extent had no significant effect on volume variability in the present cohort. Highlights: Reproducible assessment of nodule volume is essential for identification of nodule growth. Expiratory CT causes a modest but unpredictable increase in nodule volume. Emphysema surrounding nodules has no significant effect on nodule volume measurements.